2014
DOI: 10.3109/00365521.2014.920914
|View full text |Cite
|
Sign up to set email alerts
|

Palliative self-expandable metal stents for acute malignant colorectal obstruction: clinical outcomes and risk factors for complications

Abstract: The administration of CT increases the rate of stent migration, and disease control by CT can reduce the risk of obstruction by maintaining the luminal patency of palliative SEMSs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Although studies investigating the efficacy of systemic chemotherapy in patients with SEMS are limited to small sample sizes, several studies have demonstrated significantly better survival with systemic chemotherapy in patients with SEMS compared with best supportive care (BSC) [40,41]. However, systemic chemotherapy may increase the risk of SEMS-related complications, such as migration resulting from tumor response, re-obstruction due to in-and outgrowth of the tumor, and perforation, which could be potentially critical [42][43][44]. Findings in published reports (including patients with and without chemotherapy) have shown procedure-and SEMS-related complications in 5%-23% of patients, with an average rate of SEMS-related perforation in 5% of patients [12,[45][46][47].…”
Section: Previous Reports Of Systemic Chemotherapy In Patients With Semsmentioning
confidence: 99%
“…Although studies investigating the efficacy of systemic chemotherapy in patients with SEMS are limited to small sample sizes, several studies have demonstrated significantly better survival with systemic chemotherapy in patients with SEMS compared with best supportive care (BSC) [40,41]. However, systemic chemotherapy may increase the risk of SEMS-related complications, such as migration resulting from tumor response, re-obstruction due to in-and outgrowth of the tumor, and perforation, which could be potentially critical [42][43][44]. Findings in published reports (including patients with and without chemotherapy) have shown procedure-and SEMS-related complications in 5%-23% of patients, with an average rate of SEMS-related perforation in 5% of patients [12,[45][46][47].…”
Section: Previous Reports Of Systemic Chemotherapy In Patients With Semsmentioning
confidence: 99%
“…SEMS has a lower morbidity rate and similar efficacy compared with palliative surgery, avoiding unnecessary operations and providing a better quality of life. 16,22,23 A randomized control trial from 2015 24 with a sample of 56 patients with unresectable metastatic spread tried to evaluate the effect of the two palliative procedures on patients well being and symptoms relief. The quality of life scores were superior in the group of patients with SEMS comparing with the group submitted to surgical decompression, particularly in the first weeks.…”
Section: Sems (Self-expanding Metal Stent)mentioning
confidence: 99%
“…Literature searching gave rise to 207 studies, of which 10 were eligible [5,[8][9][10][11][12][13][14][15][16]. These included seven prospective cohort studies, two retrospective cohort studies and one RCT, in total 753 patients.…”
Section: Results Of Searchmentioning
confidence: 99%
“…The summary and results of methodological quality assessment of the one RCT [8] and nine observational studies [5,[9][10][11][12][13][14][15][16] are demonstrated graphically in Fig. 2.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation